Digitalization of Educational Services Marketing Program on the Primary School Teacher of Musamus University - Patawaran, Nilfred; Purwanty, Ratna; Nirtha, Eva; Ismail, My (IJBLE Scientific Publications Community Inc., 2023)
This study aims to analyze the digitalization of Musamus University's educational services marketing program. This study used an analysis model by Miles and Huberman consisting of data reduction, data presentation and taking conclusion. The approach used in this study is a qualitative approach. The subject of the study is the primary school teacher education department of Musamus University. Data collection techniques use interview techniques, document studies and literature reviews. The results of this study show that by digitalization the marketing program of the Department of Primary Teacher and Education of Musamus University has shown that the Department innovates to advance the department. Therefore, the digitalization of Musamus University's educational services marketing program help the department to improve the quality and good reputation to the society because the department not only use the manual strategy but also use the innovative strategy by using the digitalization. Eventhough in this research did not measure the effectiveness of this digitalization.